2007
DOI: 10.1111/j.1399-3038.2007.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of neutral and acidic oligosaccharides enhances Th1‐dependent vaccination responses in mice

Abstract: Immunomodulatory effects of oligosaccharide preparations that resemble chemical and functional aspects of human milk oligosaccharides (HMOS) were studied for the development of new concepts in infant nutrition. A dose range of 1-5% (w/w) dietary pectin-derived acidic oligosaccharides (AOS) was tested in a murine influenza vaccination model. In addition, combinations of AOS and a 9:1 mixture of galacto-oligosaccharides and long-chain fructo-oligosaccharides (GOS/FOS) were tested at a fixed total dietary dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 32 publications
9
79
0
Order By: Relevance
“…The scGOS/lcFOS/pAOS diet contained 2 % (9:1:1, w/w) scGOS (Vivinal GOS, FrieslandCampina Domo, Zwolle, The Netherlands), lcFOS (Raftiline HP, Orafti, Wijchen, The Netherlands) and pAOS (Südzucker AG, Mannheim, Germany (9) ). scGOS/lcFOS spray-dried powder consisted of approximately 50 % scGOS and lcFOS (9:1), 19 % maltodextrin (Glucidex 2, Roquette, France), 16 % lactose, 14 % glucose and 1 % galactose (8) .…”
Section: Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scGOS/lcFOS/pAOS diet contained 2 % (9:1:1, w/w) scGOS (Vivinal GOS, FrieslandCampina Domo, Zwolle, The Netherlands), lcFOS (Raftiline HP, Orafti, Wijchen, The Netherlands) and pAOS (Südzucker AG, Mannheim, Germany (9) ). scGOS/lcFOS spray-dried powder consisted of approximately 50 % scGOS and lcFOS (9:1), 19 % maltodextrin (Glucidex 2, Roquette, France), 16 % lactose, 14 % glucose and 1 % galactose (8) .…”
Section: Dietsmentioning
confidence: 99%
“…The combined use of neutral and acidic oligosaccharides was most effective in supporting the vaccination response in mice and has been shown to increase faecal Bifidobacteria and Lactobacilli (8,9) . The present study aims to address whether this particular scGOS/lcFOS/pAOS (9:1:1) mixture protects against the development of orally induced casein allergy in mice and to gain further insight into the underlying mechanism by which these oligosaccharides exert their effect.…”
mentioning
confidence: 99%
“…The response to vaccination of mice fed the scGOS/lcFOS diet was significant enhanced, as well as the fecal Bifidobacteria and Lactobacilli proportions. pAOS enhanced the murine vaccination response and the combination (scGOS/lcFOS/pAOS) was even more effective (Vos, Haarman et al 2007). To stimulate the entire microbiota a great variation in the oligosaccharide structures will exert this effect, as human milk oligosaccharides comprise of many different oligosaccharides.…”
Section: Nondigestible Oligosaccharidesmentioning
confidence: 99%
“…Moreover, the oligosaccharides and modified polymers from the degradation of DFs by microbiota may directly interact with the receptors in the immune cell and consequently stimulate the immune response. It has been reported that pectin derived acidic oligosaccharides (AOS), galacto-oligosaccharides (GOS) and fructooligosaccharides (FOS) can modulate the immune system in mice (Vos et al, 2007).…”
Section: Interactions Between Dietary Fiber and Microbiotamentioning
confidence: 99%
“…Next to the pectic polymers, the specific oligomers produced by microbial degradation of pectins could also potentially stimulate immune response by direct interacting with receptors on immune cells (Vos et al, 2007). The formation, identification and the time of existence in the colon before being further fermented should be studied in detail.…”
Section: Future Perspectivesmentioning
confidence: 99%